Impact Of Counseling on Compliance in Chronic Obstructive Pulmonary Disease Patients Attending General Medicine Out Patient Department in A Tertiary Care Hospital: A Prospective Study - Patel, Manish B; Patel, Monila N; Sachora, Wasimahmed M; Ghodela, Vijaykumar A (National Journal of Community Medicine, 2013)
Background-Non Compliance in patients with Chronic Obstructive Pulmonary Disease (COPD) to the medication can result in worsening of the disease and increases the hospital admissions.This study aimed to improve compliance in COPD patients. Methodology: Total 60 Patients aged 18 years & more with symptoms of dyspnea and chronic cough with or without sputum production who attended OPD from 1st march to 31staug 2011 , were counseled for compliance. Pre validated questionnaire was administered at 0 week, 2 weeks and at 6 weeks. Result: Ninety percent of the patients took the prescribed oral drugs in correct dose; correct timings and 77% complied with hospital visits. Incontrast to oral drugs only 36% of the patients were compliant to the use of inhaler at the firstvisit which improved to 59%. Life style changes related to diet and exercise were followed by 32% patients. Only 19% of patients quit smoking. In order to improve compliance levels repeatedcounseling or stressing the importance of use of inhalers and quitting smoking was found aneffective method Conclusion: This study concludes that the physicians should counsel the patient about their disease, emphasize on the medication to be taken in correct dose, timings and method of inhaler use to improve the quality of life of patients of COPD.